2007
DOI: 10.1089/cpb.2006.9984
|View full text |Cite
|
Sign up to set email alerts
|

The Unbearable Likeness of Being Digital: The Persistence of Nonverbal Social Norms in Online Virtual Environments

Abstract: Every day, millions of users interact in real-time via avatars in online environments, such as massively-multiplayer online role-playing games (MMORPGs). These online environments could potentially be unique research platforms for the social sciences and clinical therapy, but it is crucial to first establish that social behavior and norms in virtual environments are comparable to those in the physical world. In an observational study of Second Life, a virtual community, we collected data from avatars in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
251
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(283 citation statements)
references
References 29 publications
(33 reference statements)
10
251
3
2
Order By: Relevance
“…In general, the majority of studies suggest that users automatically treat computers and computer-animated agents as if they were human (Bente, Kraemer, Petersen & deRuiter, 2001;Yee, Bailenson, Urbanek, Chang, & Merget, 2007) or social actors (see "media equation"; Nass & Moon, 2000; Reeves & Nass, 1996;Gong, 2008). Users are inclined to feel empathetic with animated virtual characters (Morrison & Ziemke, 2005) and tend to feel as though they are in a social situation when a computer-animated character is displayed (Garau, Slater, Pertaub, & Razzaque, 2005).…”
Section: Different From Playing Chess: the Moral Significance Of Virtmentioning
confidence: 99%
“…In general, the majority of studies suggest that users automatically treat computers and computer-animated agents as if they were human (Bente, Kraemer, Petersen & deRuiter, 2001;Yee, Bailenson, Urbanek, Chang, & Merget, 2007) or social actors (see "media equation"; Nass & Moon, 2000; Reeves & Nass, 1996;Gong, 2008). Users are inclined to feel empathetic with animated virtual characters (Morrison & Ziemke, 2005) and tend to feel as though they are in a social situation when a computer-animated character is displayed (Garau, Slater, Pertaub, & Razzaque, 2005).…”
Section: Different From Playing Chess: the Moral Significance Of Virtmentioning
confidence: 99%
“…A significant research body on social norms in the offline world is gradually being extended into the virtual world, already finding parallels even down to eye gaze and social gestures [64] and group composition [65]. A willingness to engage online involves social pressures from the immediate social group, social identity [66] and trust in other network members [63].…”
Section: Social Normsmentioning
confidence: 99%
“…For instance, Yee, Bailenson, Urbanek, Chang, and Merget (2007) conclude that social interactions in online environments are governed by similar norms and interaction patterns as those in the physical world even though the mode of interaction differs. Additionally, McLaughlin and Vitak (2011) report that online social norm violations often resulted in similar patterns of social rejection as those that Eliasoph and Lichterman (2003) report, which suggests some level of generalizability to online collectives.…”
Section: Community Culturementioning
confidence: 99%
“…Triandis (1994) made this observation in relation to offline cultures, but the social dynamics in online collectives and groups have become increasingly similar to offline interactions (Jiang et al, 2013;Yee et al, 2007). Prior virtual community and computer-mediated communication research has demonstrated that online discussion forums have social norms that are expected to be followed and not following them may result in flaming and stronger in-group identification (Kayany, 1998;Kim, 2011).…”
Section: Interaction Of Culture-in-interaction and Occupational Culturementioning
confidence: 99%